Determination of metformin hydrochloride in human plasma by UPLC/MS/MS: Application in bioequivalence study - Mohammed, Samah Abd Elsabour; El-Dardiri, Mohammed; Elhabak, Mona Ahmed; Abu Zaid, Khaled Ibrahim (European Journal of Chemistry, 2015)
Metformin hydrochloride was quantified in human plasma by Ultra Performance Liquid Chromatography with Tandem Mass spectrometric determination (UPLC-MS/MS). The mobile phase used was (Water + 0.1% Formic acid) and (Acetonitrile + 0.1% Formic acid) in the ratio of 80:20 (v:v). An Acquity UPLC HSS T3 1.8 um 2.1×50 mm column was used. The detection was performed on a mass spectrometer (ESI+) using chlorpheniramine as an internal standard. The method was fully validated and it was applied to bioequivalence study of metformin hydrochloride in two brands of the drug with relative bioequivalence of 94.7%.